Effect of routine disinfection on bacterial composition and load of gym equipment surfaces in Qassim region, Saudi Arabia - Noorah Saleh Al-Sowayan; Shouaa Abdulaziz Alrobaish; Ghadir Ghazi Al Suliman; Jana Fahad Alharbi; Norah Sulaiman Althiwaini; Wasayf Abdulrahman Almousa; Ghuyum Suliman Alrudhayman; Meznah Naif Alsalamah; Nariman Abdullah Alharbi (Frontiers in Public Health, 2026)
Background Gym equipment surfaces represent high-contact environments that facilitate the transmission of bacterial pathogens between users. This study aimed to identify bacterial species contaminating gym equipment surfaces across six gyms in the Qassim Region, Saudi Arabia, and to evaluate the effectiveness of routine disinfection in reducing bacterial load and affecting bacterial composition. Methods Twenty-one paired surface swab samples were collected before and after routine disinfection using sterile normal saline-moistened swabs from six gyms (A–F; one male, five female) on Sunday, April 5, 2026, between 7:00 and 8:00 p.m. during peak usage hours at the end of spring. Bacterial identification was performed using the VITEK 2 automated system, and colony counts were recorded on Blood Agar. The Wilcoxon Signed-Rank Test was applied for statistical analysis. Results A total of 17 bacterial isolates were identified, distributed across three genera: Micrococcus (47.1%), Staphylococcus (47.1%), and Kocuria (5.9%). Post-disinfection colony counts decreased from 3,800 to 1,360 CFU, representing a 64.2% reduction, with a statistically significant difference ( Z = 2.671, p = 0.008). Complete elimination was not achieved on all surfaces, and the treadmill in Gym B exhibited a post-disinfection increase from 180 to 370 CFU/100 cm², which may reflect rapid recontamination, normal sampling variation, or differences in the exact surface area sampled before and after disinfection. Notably, two of the six gyms (D and F) employed multi-purpose cleaning agents devoid of any biocidal active ingredient, suggesting that their procedures may provide cleaning activity rather than confirmed disinfection activity. Conclusion These findings highlight the need for evidence-based disinfectants and standardized hygiene protocols in fitness facilities.